2009
DOI: 10.1186/1748-7161-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications in neuromuscular scoliosis operated with posterior- only approach using pedicle screw fixation

Abstract: Although posterior-only approach using pedicle screw fixation had good correction rate, complications were similar to previous reports. There were few unusual complications like coccygodynia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 40 publications
6
36
3
1
Order By: Relevance
“…The previous reports showed also that most of the major complications were respiratory. 10,15 In the present study, the Cobb angle tended to be higher in the group with major complications than the group without major complications, although this tendency was not statistically significant. Kang et al reported patients with low pulmonary function and a high Cobb angle were more likely to develop a postoperative pulmonary complication.…”
Section: Discussioncontrasting
confidence: 70%
“…The previous reports showed also that most of the major complications were respiratory. 10,15 In the present study, the Cobb angle tended to be higher in the group with major complications than the group without major complications, although this tendency was not statistically significant. Kang et al reported patients with low pulmonary function and a high Cobb angle were more likely to develop a postoperative pulmonary complication.…”
Section: Discussioncontrasting
confidence: 70%
“…Um estudo de Modi et al 8 avaliou complicações cirúrgicas em 50 casos de escoliose neuromuscular tratados por via posterior somente (não havendo pacientes com mielomeningocele) e constatou 6% de complicações com a ferida operatória, sendo um caso de infecção profunda, um superficial e um caso de deiscência da ferida. Considerando os fatores de risco para complicações gerais, eles concordaram com Sponseller et al 2 que a magnitude da curva escoliótica não aumenta o risco de complicações porém, discordaram em outros fatores, relatando que o uso de aloenxerto não é fator e que a perda sanguínea maior que 3500ml é um fator de risco.…”
Section: Objetivo: Las Cirugías De La Columna Vertebral Realizadas Enunclassified
“…Attention to padding is important to avoid complications such as coccygodynia. 47 Reassessment of the hips should be performed to determine the need for tenotomies to address contractures that may become more prominent after surgery.…”
Section: Other Postoperative Considerationsmentioning
confidence: 99%